Genetically engineered trees for plantation forests: key considerations for environmental risk assessment. Issue 7 (5th August 2013) - Häggman, Hely; Raybould, Alan; Borem, Aluizio; Fox, Thomas; Handley, Levis; Hertzberg, Magnus; Lu, Meng‐Zu; Macdonald, Philip; Oguchi, Taichi; Pasquali, Giancarlo; Pearson, Les; Peter, Gary; et al.
Summary Forests are vital to the world's ecological, social, cultural and economic well‐being yet sustainable provision of goods and services from forests is increasingly challenged by pressures such as growing demand for wood and other forest products, land conversion and degradation, and climate change. Intensively managed, highly productive forestry incorporating the most advanced methods for tree breeding, including the application of genetic engineering (GE), has tremendous potential for producing more wood on less land. However, the deployment of GE trees in plantation forests is a controversial topic and concerns have been particularly expressed about potential harms to the environment. This paper, prepared by an international group of experts in silviculture, forest tree breeding, forest biotechnology and environmental risk assessment (ERA) that met in April 2012, examines how the ERA paradigm used for GE crop plants may be applied to GE trees for use in plantation forests. It emphasizes the importance of differentiating between ERA for confined field trials of GE trees, and ERA for unconfined or commercial‐scale releases. In the case of the latter, particular attention is paid to characteristics of forest trees that distinguish them from shorter‐lived plant species, the temporal and spatial scale of forests, and the biodiversity of the plantation forest as a receiving environment.